2018
DOI: 10.12998/wjcc.v6.i11.418
|View full text |Cite
|
Sign up to set email alerts
|

Dual HER2 inhibition strategies in the management of treatment-refractory metastatic colorectal cancer: History and status

Abstract: Human epidermal growth factor receptor 2 (HER2) signaling pathway activation has been identified as a contributor to de novo or acquired resistance to epidermal growth factor receptor (EGFR) inhibitors in a small subset of patients with metastatic colorectal cancer (mCRC). Dual anti-HER2-targeted treatment exhibits strong antitumor activity in preclinical models of HER2-positive mCRC, supporting its testing in clinical trials. The HERACLES trial at four Italian academic cancer centers has confirmed the effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…A number of studies revealed the presence of HER2 amplification and/or activation by overexpression of the HER3/4 ligand, heregulin, in CRC patient samples or patient-derived xenograft models with acquired resistance to anti-EGFR treatment [36,37,38,48]. Among the EGFR family, HER2 is the one with the strongest catalytic activity and it usually dimerizes with EGFR (HER1) and HER3 [17].…”
Section: Acquired Resistance To Anti-egfr Treatment In Crc Patientsmentioning
confidence: 99%
“…A number of studies revealed the presence of HER2 amplification and/or activation by overexpression of the HER3/4 ligand, heregulin, in CRC patient samples or patient-derived xenograft models with acquired resistance to anti-EGFR treatment [36,37,38,48]. Among the EGFR family, HER2 is the one with the strongest catalytic activity and it usually dimerizes with EGFR (HER1) and HER3 [17].…”
Section: Acquired Resistance To Anti-egfr Treatment In Crc Patientsmentioning
confidence: 99%
“…In the past two decades, systemic chemotherapy b one of the foremost choices for advanced CRC treatment 36. Recently, molecule-targeted agents, such as cetuximab,37 panitumumab,38,39 bevacizumab,40 regorafenib41,42 and ramucirumab,43,44 that inhibit RTKs activation have been approved for use in CRC treatment. Downregulation of RTKs’ activity can attenuate tumor cell growth, metastasis, and angiogenesis 4547.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, molecular-targeted agents [17], such as cetuximab and panizumab [18], bevacizumab [19,20], regofenib [21] , remoluzumab [22,23] and RTKs [24,25] have been used clinically in the treatment of CRC. However, little research has been done on multidrug-resistant cells in colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%